Thermal Characterization Of Power LEDs And LED Assemblies - Permal, Anithambigai (2012)
As the technology of light emitting diode (LED) improves, the amount of heat generated becomes a bottleneck to the technology that affects the reliability, stability and lifetime of the device. Therefore, to sustain the performance of a product, thermal management of power LEDs has become very significant. Both junction temperature (TJ) as well as thermal resistance (Rth) are the key evaluation parameters in the study of thermal management. The goal of this research is to understand the thermal characteristics of power LEDs under various conditions which could enhance the understanding towards better thermal management.